Analisis Strategi Office Channeling dalam Meningkatkan Penjualan Tabungan iB Syariah pada CIMB Niaga Syariah - Emilia Embun Sari (MAN 4 Kota Pekanbaru, 2026)
This study examines the “Dual Banking Leverage Model (Office Channeling)” strategy for CIMB Niaga Syariah's IB Savings product sales, a leading strategy for CIMB Niaga Syariah to increase Third Party Funds (DPK), specifically for its IB Syariah Savings product. This study uses a descriptive qualitative analysis method that systematically, timely, and reliably describes the relationships between the phenomena studied. CIMB Niaga Syariah uses the Dual Banking Leverage Model (DBLM) through Office Channeling to implement its IB Savings product marketing strategy. This strategy expands sales of IB Syariah Savings products beyond Sharia branches to include conventional branch channels. The results of the discussion show that the Office Channeling Strategy is a superior strategy that contributes very relevantly to increasing Sharia Third Party Funds, especially for Ib Savings products at CIMB Niaga Syariah.